Room evacuation in the presence of an obstacle - Frank, Guillermo Alberto (2011)
The investigation of human behaviour while trying to escape from a room under panic is an important issue in complex systems research. Several authors have called attention to the fact that placing an obstacle near the exit improves the evacuation time of the room (Helbing et al. (2000, 2005) [2,8], Hughes (2003) [6], Johansson and Helbing (2005) [16], Piccoli and Tosin (2009) [5]). We studied this effect in the context of the "social force model" (Helbing et al. (2000) [2]). We show that placing an obstacle does not guarantee, by itself, better chances of survival for all pedestrians. The way they choose to avoid the obstacle is critical for their own performance. We found not only that the faster they try to escape, the slower they get out ("faster is slower" effect), but also, the short cut they might take in order to get to the exit will probably do no better ("clever is not always better" effect). © 2011 Elsevier B.V. All rights reserved.